The EU Vaccines Strategy: A mixed bag of achievements and discontent - Jane Arroyo; Chiara Del Giovane; Berta Mizsei; Hien Vu; Timothy Yu-Cheong Yeung (European Journal of Risk Regulation)
During the COVID-19 pandemic, the European Union (EU) observed a major centralisation of competence in public health policy – the EU Vaccines Strategy. Yet increased centralisation or integration is not always desirable because the EU lacks a layer of democratic control to ensure transparency and accountability. This feature highlights the need to better understand and assess the EU’s actions during the pandemic. This paper aims to assess the effectiveness of the EU Vaccines Strategy and contributes to the wider debate on the centralisation of power at Union level. The joint procurement of COVID-19 vaccines is considered a success, as it avoided a “vaccine scramble” by the EU Member States. However, the fact that the Member States were obliged to purchase more than they needed and the lack of transparency in the negotiations with companies on the procurement of vaccines have raised questions about the integrity of the Commission’s exercise of executive power.